2016
DOI: 10.1177/1757913916636925
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of eating habits, body weight and television programme preferences on television viewing time and domestic computer usage

Abstract: In order to reduce total screen time, health interventions should target different types of screen viewing audiences separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Seven indicators were included in this scale to measure consumption frequencies of specific food groups, such as wholegrain bread (including multigrain bread, wholegrain and multigrain rolls), white-toasted bread (white bread and rolls), fresh fruit, fresh and frozen vegetables, meat and processed meat products (e.g., sausages), deep fried foods (e.g., chips and crisps), and confectionery (sweets, cakes, biscuits, pastries). These indicators were constructed for GESIS-General Social Surveys and mapped basic nutritional categories [ 49 , 51 ]. All the items were scored on a seven-point frequency scale ranging from several times a day to never (several times a day, every day/almost every day, several times a week, about once a week, two or three times a month, once a month or less often, or never).…”
Section: Methodsmentioning
confidence: 99%
“…Seven indicators were included in this scale to measure consumption frequencies of specific food groups, such as wholegrain bread (including multigrain bread, wholegrain and multigrain rolls), white-toasted bread (white bread and rolls), fresh fruit, fresh and frozen vegetables, meat and processed meat products (e.g., sausages), deep fried foods (e.g., chips and crisps), and confectionery (sweets, cakes, biscuits, pastries). These indicators were constructed for GESIS-General Social Surveys and mapped basic nutritional categories [ 49 , 51 ]. All the items were scored on a seven-point frequency scale ranging from several times a day to never (several times a day, every day/almost every day, several times a week, about once a week, two or three times a month, once a month or less often, or never).…”
Section: Methodsmentioning
confidence: 99%
“…Differences related to screen activity type may be explained by other activities done at the same time, such as eating while watching television, which is less likely when using the computer [ 32 ]. Additionally, TV viewing is a passive activity that often takes an hour or more at a time, while most computer use requires active interaction, and may be done for short but recurring periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, some questions remain to be answered, especially regarding the difference in the association between males and females, which was examined in few studies with inconsistent findings [ 29 , 31 , 34 , 35 ]. Additionally, the potential interaction between screen time and other risk factors for obesity, namely physical activity and sleep duration, has not been adequately explored in adolescents, although a few studies indicated that adequate physical activity may attenuate the effects of increased screen time [ 32 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation